Development Of EZ DNA Diagnostic Kit For The Detection Of Homozygous Deletion Of SMN1 Gene In Spinal Muscular Atrophy (SMA) Patients - Marzuki, Marini (2012)
Spinal Muscular Atrophy (SMA) is the second most frequent fatal autosomal recessive disorder of childhood. The incidence of this disease is approximately 1 in 10000 live births. SMA is characterized by progressive muscle weakness resulting from degeneration and loss of motor neurons in the anterior horn of spinal cord. The responsible genes for SMA are Survival of Motor Neuron (SMN). SMN1 and SMN2 genes share over 99.8% sequence homology and they can be distinguished by base changes in both exons 7 and 8. SMN1 gene is not detectable in majority of SMA cases due to either deletion or conversion. Conventionally, the homozygous deletion of SMN1 gene is detected using Polymerase Chain Reaction-Restriction Enzyme (PCR-RE) method. This method is time consuming, expensive and requires restriction enzyme digestion and a considerably high amount of amplified DNA to be visible after digestion. This may lead to false-negative results. To avoid these problems, we have developed an alternative method using an allele-specific primer for the molecular diagnosis of SMA which is more time-saving and cost-effective. The freeze dry platform was applied to the multiplex AS-PCR for the development of a thermostabilize diagnostic kit. A total of one hundred and forty three samples of clinically suspected SMA were included in this study. Conventional molecular diagnosis using PCR-RE was done to detect the presence or absent of SMN1 deletion in these samples.